2017
DOI: 10.1299/transjsme.16-00523
|View full text |Cite
|
Sign up to set email alerts
|

Axle box suspensions using magnetic elastomers with variable elasticity

Abstract: We have devised a steering system in which the magnetic elastomer is used for the elastic members such as rubber bushings in the axle box suspension of railway vehicles. The magnetic elastomer is composed of magnetic particles and the elastomer such as synthetic rubber. This material is characterized by its hardness variation depending on the magnetic field. The axle box suspension using the magnetic elastomer is capable of varying the longitudinal stiffness. In straight sections, the application of this axle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…It was observed that the outer wheel lateral force at 0 mT was reduced in the circular curve section (distance: 150 ~ 300 m) by approximately 20% compared to that at 389 mT. From the previous simulation results [21], it is inferred that the mobility of the wheelsets changed due to the change in the elastic modulus depending on the presence or absence of the magnetic field, although it is possible that the causes of the change in lateral force may include the influence of the friction coefficient produced by the temperature or the humidity on the test day. Moreover, from the result of the displacement of the magnetic elastomer bushing at 0 mT, it is evident that it is easily affected by track irregularity due to the reduction of the longitudinal stiffness of the mono-link.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…It was observed that the outer wheel lateral force at 0 mT was reduced in the circular curve section (distance: 150 ~ 300 m) by approximately 20% compared to that at 389 mT. From the previous simulation results [21], it is inferred that the mobility of the wheelsets changed due to the change in the elastic modulus depending on the presence or absence of the magnetic field, although it is possible that the causes of the change in lateral force may include the influence of the friction coefficient produced by the temperature or the humidity on the test day. Moreover, from the result of the displacement of the magnetic elastomer bushing at 0 mT, it is evident that it is easily affected by track irregularity due to the reduction of the longitudinal stiffness of the mono-link.…”
Section: Resultsmentioning
confidence: 95%
“…If the elastic modulus of the materials embedded in the mono-link can be changed freely, the vehicle will have less friction in curved sections and high stability when travelling in a straight line by optimizing the elasticity of the material. The results obtained from our numerical simulation [21] revealed that the material of this actuator needs an off-field modulus higher than few 100 kPa and high relative changes in the modulus 2–5-fold higher than the off-field modulus. This material can reduce the lateral force acting on the outer rail by 20% in a curved section with a radius of curve of 200 m. In this study, we did not prepare a magnetic circuit that is a special for railway actuators.…”
Section: Introductionmentioning
confidence: 99%